Fatty acid regulation and phosphatidylethanolamine biosynthesis are important for hepatitis E virus replication - Kush K. Yadav; Menuka Bhandari; Hassan M. Mahsoub; Young Bin Park; Huong Van Le; Jae Mun Choi; Hannah M. Brown; Gireesh Rajashekara; Scott P. Kenney; Xiang-Jin Meng (Proceedings of the National Academy of Sciences, 2026)
Hepatitis E virus (HEV), a leading cause of viral hepatitis globally, is associated with adverse outcomes during pregnancy. Despite its clinical significance, the mechanisms driving enhanced HEV replication during pregnancy remain poorly understood. In this study, we uncover a lipid-mediated pathway that facilitates HEV replication, with potential implications for pregnancy-associated pathogenesis. Lipidomic profiling reveals a marked upregulation of oleic acid during HEV infection in both human liver cells and in HEV-3ra-infected pregnant rabbits. We showed that oleic acid significantly enhances HEV replication, possibly through interaction with a predicted fatty acid–binding domain (FABD) located within the papain-like cysteine protease region of the HEV ORF1 polyprotein. We further demonstrated that phosphatidylethanolamine (PE) levels are elevated during HEV-3ra infection in pregnant rabbits, and that inhibition of PE biosynthesis by CRISPR/Cas9-mediated knockdown and silencing of phosphatidylserine decarboxylase/phosphoethanolamine cytidylyltransferase genes that are responsible for PE synthesis resulted in decreased HEV replication, indicating that PE is important for HEV replication. Additionally, we found that placental lactogen hormone, which is elevated during late pregnancy, stimulated fatty acid accumulation and potentiated HEV replication, therefore providing a potential explanation for pregnancy-associated adverse outcomes. Collectively, our findings reveal an important role of host lipid metabolism in HEV replication and offer mechanistic insights into lipid-dependent enhancement of HEV replication and a potential role of lipid reprogramming in HEV pathogenesis. The results may inform potential future anti-HEV therapeutic strategies targeting lipid pathways.